Global experience in development and performance of nongovernmental organizations - Ospanova, D.K. (Ye.A.Buketov Karaganda State University Publ., 2012)
In this article we take into consideration the experience gained by foreign social institutions on solving of various issues in society. The urgency of this research is determined by the alternative pattern of political system transformation in the Republic of Kazakhstan. The author tries to succeed in identifying principles of nongovernmental organization development as a phenomenon of political system in modern Kazakhstan. Global civil society must be formed according to either a western institutional pattern or have regard to main traditions and institutions in our state.
Үкіметтік емес ұйымдардың дамуы мен қызмет етуінің əлемдік тəжірибесі
Мировой опыт развития и функционирования неправительственных организаций
Keywords: political system transformation; global experience; political system in modern Kazakhstan; NGO; nongovernmental organization development